Spiritualitas Guru Agama Katolik dalam Pelayanan Hidup Menggereja di Wilayah Perbatasan Kabupaten Sanggau - Mayong Andreas Acin; Florensius Sutami (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2022)
The spirituality of Catholic religious teachers in the ministry of living in the church is living in the Holy Spirit. The Holy Spirit helps and renews the teacher of the Catholic religion constantly in his special identity, in his vocation and mission. With the help and renewal of the Holy Spirit, a Catholic religion teacher experiences a new and special motivation, a call to holiness of life. Thus a Catholic religion teacher is not only an ordinary educator, but he himself is an educator accompanied by the Holy Spirit. Our Lady is an example of faith for all. His surrender to divine providence leads him to the mystery of salvation. This research applied a qualitative approach. The hypothesis testing and statistical analysis was applied. This study described the phenomena of spirituality of the Catholic religious teachers and the factors that cause the spirituality of Catholic religious teachers, and what was appropriate to do to improve the spirituality of Catholic religious teachers in the ministry of life. church in the border region. This research cannot be separated from the use of scientific principles as a guide so that research activities can be carried out properly. Data collection methods or techniques used are observation, interviews, and documentation. The results of this scientific research were expected to be a reference or guide in improving the spirituality of Catholic religious teachers, especially to Catholic religious teachers in the ministry of living in the church in border areas. This research is useful for STAKatN Pontianak, to provide input on the importance of the spirituality of Catholic religious teachers in the ministry of church life in border areas.